Fishermen’s memories: rediscovering the history of the community of Lobitos, Peru - Gonzales, Amanda (2017)
This article presents the methodology and main results of a research/action project called “Fishermen’s Memories”, conducted by the two authors in the coastal town of Lobitos (Northern Peru). The project aims to reconstruct the history of Lobitos basing itself on the voices of members of the local fishing community, in order to highlight their own narratives and vision of the past and enable them to transmit these to the younger generations. After presenting the goals, methodology and context of the project, we reflect upon some of the main results of our research and try to explore the defining elements of this community’s identity and the way it perceives and analyzes its history. Finally, we describe the work that was carried out with the participants and present the main products of the project as well as its future prospects.